2020
DOI: 10.1016/j.msec.2019.110267
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the application of mesoporous silica-based nanomaterials for bone tissue engineering

Abstract: Silica nanomaterials (SNMs) and their composites have recently been investigated as scaffolds for bone tissue engineering. SNM scaffolds possess the ability to encourage bone cell growth and also allow the simultaneous delivery of biologically active biomolecules that are encapsulated in the mesopores. Their high mechanical strength, low cytotoxicity, ability to stimulate both the proliferation and osteogenic differentiation of progenitor cells make the SNMs appropriate scaffolds. Their physiochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 146 publications
(93 citation statements)
references
References 120 publications
(119 reference statements)
0
92
0
1
Order By: Relevance
“…60 and 120 C, a gradual weight loss has emerged that is attributed to the separation of the captured water molecules in the silica network of the VP, which performances as an excessive molecular sieve. 56 In the range of 120 to 500 C, an excellent weight loss has been appeared for the curve related to the VP/CTS and Ag@VP/CTS composites, which is accredited to the loss of the -OH groups present in the CTS structure. According to the literature, at this range, the hydroxyl groups of the polymeric chains are removed as the hydrate molecules.…”
Section: Characterizationmentioning
confidence: 95%
“…60 and 120 C, a gradual weight loss has emerged that is attributed to the separation of the captured water molecules in the silica network of the VP, which performances as an excessive molecular sieve. 56 In the range of 120 to 500 C, an excellent weight loss has been appeared for the curve related to the VP/CTS and Ag@VP/CTS composites, which is accredited to the loss of the -OH groups present in the CTS structure. According to the literature, at this range, the hydroxyl groups of the polymeric chains are removed as the hydrate molecules.…”
Section: Characterizationmentioning
confidence: 95%
“…The peaks related to melamine structure after CA reaction appeared at 29°and 31°, were covered by a broad peak at 30 figure 8(a) that shows the obtained results from thermogravimetric analysis (TGA). As seen in the curves, the weight of the Fe 3 O 4 /SiO 2 /C=C NPs is gradually decreased that is related to the both physically adsorbed and entrapped water molecules onto the surfaces and into the silica network [35]. Almost 8% of the weight loss was observed in a thermal range of 50°C-580°C.…”
Section: Fluorescence Spectroscopymentioning
confidence: 89%
“…Recent studies have found that cells can be driven to the center of the three-dimensional scaffold with the help of magneto-mechanical drive. Parfenov et al reported a technique of using magnetic force to seed cells, using a porcine acellular common carotid artery stent (Eivazzadeh-Keihan et al, 2020 ; Parfenov et al, 2020 ). The porcine acellular common carotid artery stent was immersed in a suspension of magnetically labeled cells.…”
Section: Preparation Of Magnetic Nanomaterialsmentioning
confidence: 99%